The Effects of Corrosive Chemicals on Corrosion Rate of Steel Reinforcement Bars: II. Swamp Sludges - Ashadi, Henki W.; Widanarko, Sulistyoweni; Gusniani, Irma (UI Scholars Hub, 2002)
A polluted environment will influence the building age. The objective of this research was to find out the influence of corrosive chemicals within the sludge swamp area with the corrosion rate of steel concrete. Corrosion in steel concrete usually occur in acid area which contain of SO4 2-, Cl- and NO3 -. The research treatment used by emerging ST 37 and ST 60 within 60 days in ‘polluted’ sludge swamp area. Three variation of ‘polluted’ swamp sludge were made by increasing the concentration a corrosive unsure up to 1X, 5X and 10X. The corrosion rate measured by using an Immersion Method. The result of Immersion test showed that sulphate had a greatest influence to corrosion rate of ST 37 and ST 60 and followed by chloride and nitrate. Corrosion rate value for ST 37 was 17.58 mpy and for ST 60 was 12.47 mpy.